The Influence of Islamic Financial Literacy and Mob Mentality on Behavioral Intention to Conduct Transactions Using E-Wallets Mediated by Perceived Risk - Ramadani, Ilham; Iiz iIzmuddin (Universitas Yudharta Pasuruan, 2025)
Introduction; The rapid adoption of e-wallets among Generation Z in Indonesia presents new challenges in aligning financial behavior with Islamic principles. This study examines the effect of Islamic Financial Literacy and Mob Mentality on Behavioral Intention to use e-wallets, with Perceived Risk as a mediating variable, focusing on Generation Z Muslim users in Bukittinggi City. Method; This quantitative study used a field research design involving 288 Generation Z Muslim respondents in Bukittinggi City. The variables include Islamic Financial Literacy (X1), Mob Mentality (X2), Behavioral Intention (Y), and Perceived Risk (Z). Data were collected using Likert-scale questionnaires distributed via Google Forms, with purposive and convenience sampling. Analysis was conducted using Warp Partial Least Squares (WarpPLS) 7.0. Results: Both Islamic Financial Literacy and Mob Mentality significantly influence the behavioral intention of Generation Z Muslims to use e-wallets. Higher financial literacy and social influence encourage greater intention to transact. Perceived Risk acts as a key mediator that strengthens these relationships, showing that digital financial behavior is shaped by knowledge, social dynamics, and risk perception. Conclusion; Islamic Financial Literacy and Mob Mentality play essential roles in shaping Muslim Generation Z’s intention to use e-wallets, with Perceived Risk serving as a mediating factor. The study contributes to Islamic finance and behavioral research and offers practical insights for promoting financial literacy and ethical digital transactions among young Muslim consumers.